Music, dhikr, and deep breathing technique to decrease depression level in older adults: Evidence-based practice in Depok City, Indonesia - Bahtiar, Bahtiar; Sahar, Junaiti; Widyatuti, Wdiyatuti (UI Scholars Hub, 2020)
Depression is a mental health problem that affects the elderly. As meeting the spiritual needs of depressed older people is important, a spiritual approach nursing intervention must be applied to reduce the level of depression in this population. This study proposed an integrated spiritual nursing approach through music therapy, dhikr, and deep breathing to improve depression levels among the elderly living in Cisalak Pasar, Depok City, in 2019. The research method used was a case study of an evidence-based practice using the Geriatric Depression Scale. The study sample consisted of 106 elderly, who were recruited by purposive sampling. The average depression scores among the elderly were 4.79 and 2.48 before and after the intervention, respectively, indicating that the mean depression score decreased by 2.31. The independent t-test results obtained a p-value < 0.05, demonstrating the positive influence of the proposed spiritual approach nursing intervention on the level of depression among the subjects. A spiritual approach nursing intervention program through music therapy, dhikr, and deep breathing reduced the level of depression in the elderly. Thus, such an approach can be used as an intervention option in dealing with depression problems in the elderly.